Recent Advances in Metabolic Engineering, Protein Engineering, and Transcriptome-Guided Insights Toward Synthetic Production of Taxol - Mutanda, Ishmael; Li, Jianhua; Xu, Fanglin; Wang, Yong (Frontiers in Bioengineering and Biotechnology, 2021)
The diterpenoid paclitaxel (Taxol®) is a blockbuster anticancer agent that was originally isolated from the Pacific yew (Taxus brevifolia) five decades ago. Despite the wealth of information gained over the years on Taxol research, there still remains supply issues to meet increasing clinical demand. Although alternative Taxol production methods have been developed, they still face several drawbacks that cause supply shortages and high production costs. It is highly desired to develop biotechnological production platforms for Taxol, however, there are still gaps in our understanding of the biosynthetic pathway, catalytic enzymes, regulatory and control mechanisms that hamper production of this critical drug by synthetic biology approaches. Over the past five years, significant advances were made in metabolic engineering and optimization of the Taxol pathway in different hosts, leading to accumulation of taxane intermediates. Computational and experimental approaches were leveraged to gain mechanistic insights into the catalytic cycle of pathway enzymes and guide rational protein engineering efforts to improve catalytic fitness and substrate/product specificity, especially of the cytochrome P450s (CYP450s). Notable breakthroughs were also realized in engineering the pathway in plant hosts that are more promising in addressing the challenging CYP450 chemistry. Here, we review these recent advances and in addition, we summarize recent transcriptomic data sets of Taxus species and elicited culture cells, and give a bird’s-eye view of the information that can be gleaned from these publicly available resources. Recent mining of transcriptome data sets led to discovery of two putative pathway enzymes, provided many lead candidates for the missing steps and provided new insights on the regulatory mechanisms governing Taxol biosynthesis. All these inferences are relevant to future biotechnological production of Taxol.